A winter double daisy - Gray, Kes (Red Fox London, 2015)
Daisy's getting into double the trouble in this fantastic collection! Whether she's tracking down thieves in 'Daisy and the Trouble With Burglars' or starring in her school nativity play in 'Daisy and the Trouble With Christmas', one thing's for sure there's always trouble when Daisy's about